Impact Assessment of Water Crisis on Socio Economic Life of Agrarian Community - Sabir, Raja Irfan; Irfan , Muhammad; Akhtar, Naeem; Nawaz, Farooq; Shahnawaz, Muhammad (Asian Journal of Agriculture and Rural Development, 2014)
The objectives of the present study will be to explore the effects of scarcity of water on farmers’ socio economic values & standard of living while taking adoption of water saving technologies or better water resource management plan by farmers as moderating variable. A sample of 150 household farmers in district Okara was selected through multistage sampling techniques. A well structured questionnaire was designed on five point licker scale covering various dimensions of water crises and their impact on socio economic dimension of farmer’s lives. For data analysis quantitative techniques of multiple regression & regression for moderation were applied by using SPSS 16.